PENDIDIKAN MASYARAKAT TENTANG PENYELENGGARAAN JENAZAH DI DESA SIALANG PANJANG KABUPATEN INDRAGIRI HILIR – RIAU - Syamsiah Nur; Faridatul Munawaroh (Jurnal Abdi Masyarakat, 2025)
The increasing indifference of society, especially mothers, is very worrying for many parties. Regarding knowledge and practice in handling corpses. Even though various efforts have been made, until now the number of incidents is still difficult to reduce. The activities provided to mothers, such as training, are still not running optimally. The aim of this community service is to optimize mothers' knowledge regarding funeral arrangements. The method used is through interactive discussions about the management of corpses. The result of this community service activity is that most of the mothers' knowledge after the training is very good. The mothers felt that the training activities on funeral arrangements were very useful, the mothers really wanted this activity not to stop here, but to continue